2021
DOI: 10.3389/fpubh.2021.623685
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Adolescents Living in Rural and Urban New Caledonia: The Role of Socioenvironmental Factors and the Association With Weight Status

Abstract: Physical activity (PA) is an important factor for the prevention of overweight and obesity, particularly during adolescence. This study focuses on the understudied adolescent population of New Caledonia with the aim to (1) determine the daily PA levels and estimate the sedentary time through out-of-school sitting time; (2) highlight the influence of sociodemographic and environmental factors, and (3) assess the associations of PA and sitting time with overweight and obesity. A sample of 508 school-going adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
3
10
0
1
Order By: Relevance
“…Another barrier experienced by ONENA youth was safety, which led to the facilitators that highlighted the importance of parent and community member engagement with youth in PA and sport. This finding is supported by another study conducted with adolescents living in rural and urban New Caledonia (a PICT), which indicated that safety was an important driver for engagement in PA, particularly for younger children and adolescent females [ 35 ].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Another barrier experienced by ONENA youth was safety, which led to the facilitators that highlighted the importance of parent and community member engagement with youth in PA and sport. This finding is supported by another study conducted with adolescents living in rural and urban New Caledonia (a PICT), which indicated that safety was an important driver for engagement in PA, particularly for younger children and adolescent females [ 35 ].…”
Section: Discussionsupporting
confidence: 52%
“…However, an evaluation of program efficacy found that these school-based PA programs were limited by low participation rates and reach. Only two studies conducted in New Caledonia showed the effectiveness of a digital PA intervention among ONENA adolescents [ 32 ], as well as the influence of socioeconomic status, place of living (e.g., tribal, rural, urban), ethnicity (European, ONENA, Asian), and safety in urban areas on PA for adolescents [ 32 , 33 , 34 , 35 ]. Therefore, little is known about the barriers to and facilitators of PA faced by ONENA adolescents residing in PICT and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, many children and adolescents are developing diabetes which is a major health concern 32,33 . The way of living of children and adolescents has changed due to modernization, availability of ready-to-eat food, fast urban expansion, and reduced physical activity [34][35][36] . Because SEA communities have a immense genetic propensity for metabolic abnormalities like diabetes and CVD, the health impacts are severe 37 .…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Physical activity plays a signi cant role in maintaining the health of adolescents and preventing overweight and obesity [11], while according to WHO data [12], children and adolescents who engage in a minimum of 60 minutes of moderate to vigorous physical activity have no risk of overweight and obesity. The bene ts of physical activity are numerous, including improvements in physical tness (including cardiorespiratory and muscular tness), maintenance of normal blood pressure, dyslipidemia, glucose, insulin resistance, better bone health, cognitive outcomes, mental health, and more [13].…”
Section: Introductionmentioning
confidence: 99%